Pedagogical Challenges Encountered by Teachers in Some Content Areas of the Reintroduced History Curriculum in Junior Secondary Schools in Awka Education Zone - Chukwuka Judith Nkolika (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: In recent years, there has been a renewed emphasis on history education in Nigeria’s basic education curriculum, driven by the recognition of its role in fostering national identity, civic responsibility, and critical thinking among young learners. However, the reintroduction of history as a standalone subject has presented several pedagogical challenges for teachers, particularly in terms of content delivery and resource availability. Objective: This study aims to identify the pedagogical challenges faced by teachers in delivering the reintroduced basic education history curriculum in the Awka Education Zone, Nigeria. Method: A descriptive research design was used, involving 53 history teachers from 53 public secondary schools. Since the population was manageable, no sampling was conducted. 50 completed questionnaires were analyzed using descriptive statistics (Mean and Standard Deviation), and internal consistency was measured using Cronbach Alpha, yielding a reliability score of 0.91. Result: Teachers faced difficulties in teaching differences among pre-colonial Nigerian civilizations, the evolution of the Nigerian state, and the centralization of power and authority. Conclusion: Addressing these teaching challenges requires enhanced support and resources for history educators. Contribution: The study highlights the need for government funding, financial support, and budget allocation to provide materials for student assessment and improve history education quality.